2020
DOI: 10.7554/elife.58360
|View full text |Cite
|
Sign up to set email alerts
|

A new no-report paradigm reveals that face cells encode both consciously perceived and suppressed stimuli

Abstract: A powerful paradigm to identify neural correlates of consciousness is binocular rivalry, wherein a constant visual stimulus evokes a varying conscious percept. It has recently been suggested that activity modulations observed during rivalry may represent the act of report rather than the conscious percept itself. Here, we performed single-unit recordings from face patches in macaque inferotemporal (IT) cortex using a no-report paradigm in which the animal’s conscious percept was inferred from eye movements. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
4
32
1
Order By: Relevance
“…in its contrast or intensity). This is clearly demonstrated in binocular rivalry experiments ( Blake 2001 ; Hesse and Tsao 2020 ) in which a physically unchanging stimulus alternates between being consciously visible and invisible.…”
Section: Aa and Perceptual Consciousnessmentioning
confidence: 90%
“…in its contrast or intensity). This is clearly demonstrated in binocular rivalry experiments ( Blake 2001 ; Hesse and Tsao 2020 ) in which a physically unchanging stimulus alternates between being consciously visible and invisible.…”
Section: Aa and Perceptual Consciousnessmentioning
confidence: 90%
“…Yet, previous research has repeatedly shown that prefrontal cortex may indeed represent the contents of conscious experience 51,52 . Intersecting computational models of dynamic conflict-accumulation 14 with no-report paradigms of bistable perception will enable future research to test whether the contents of conscious experience are represented 53 or multiplexed 54 within the neural correlates of perceptual conflict, creating exciting new opportunities to better understand the role of prefrontal cortex in consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies optimized for decoding have repeatedly shown that prefrontal cortex may indeed encode the contents of conscious experience 47,48,65 and may thus constitute a true neural correlate of consciousness. 47,48 Intersecting computational models of dynamic conflict accumulation 13 with noreport paradigms of bistable perception will enable future research to test whether the contents of conscious experience are represented 48 or multiplexed 69 within the neural correlates of perceptual conflict, creating exciting new opportunities to better understand the role of prefrontal cortex in consciousness.…”
Section: Ifc Regulates the Access Of Conflicting Information Into Conscious Experiencementioning
confidence: 99%